Solid Waste Management Practices at The Academic Institution: Current Situation and Strategic Plan - Euis Nurul Hidayah; Imroatul Mufidah; Indah Fitriana Solichah; Okik Hendriyanto Cahyonugroho; Kindriari Nurma Wahyusi (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Waste management is one of the actionsof environmental management for improving environmental quality. This study describes the waste management in the campus through improvement of operational techniques, starting from container, collection, and transportation. Case study was taken in the university, which the amount of waste generation is about 166.559 kg/day or 0.013 L/person/day. The waste collection system is designed to use individual disaggregated sorting patterns that are adjusted to the composition of the waste, colour differentiation, and label of the container. Amount of sorted containers are 478 pieces. The waste collection system is planned by an indirect individual collection pattern and a temporary shelter plan in the form of a partition wall is adjusted to the composition of the waste. Planning for waste transportation system is using a fixed container system with motor cart under capacity of 2.3 m3 with 1 fleet. Transportation is carried out on a scheduled basis. Transportation management is arranged twice per-day for organic waste, once per-day for valuable waste, once per-week for hazardous waste, once every 2 days for other water. Transportation schedule is carried out twice per-day, in the morning and evening.